Face mask and emotion discrimination: a duchenne smile study - Pinto, Nicolle Galperin Gomes (2022)
Master's dissertation and presented at ISPA – Instituto Universitário in order to obtain a master’s degree in the specialty of Cognitive and Behavioral Neurosciences, on the year of 2021.